Assessment of Professional Quality of Life in the Alabama Physical Therapy Workforce. Issue 7 (8th March 2021) - Bowens, Andrea N; Amamoo, M Ahinee; Blake, Dana Daniel; Clark, Bethany
Abstract: Objective: The purposes of this study were to 1) determine the level of professional quality of life among physical therapists and physical therapist assistants in Alabama and 2) to identify personal or professional factors that may contribute to compassion satisfaction (CS), burnout, and secondary traumatic stress (STS). Methods: This study used a cross-sectional design and mixed-methods survey methodology to calculate odds ratios for factors affecting professional quality of life. Respondents completed a survey that included the Professional Quality of Life (ProQOL) scale, an open-ended question regarding their experience with professional burnout, and personal and professional demographics. Results: Of the 742 physical therapists and physical therapist assistants in Alabama who completed the survey, the majority experienced moderate-high levels of CS and moderate-low levels of burnout and STS. Regression analyses indicated clinicians working 40 or more hours per week in patient care had greater odds for low-moderate CS and moderate-high burnout and STS subscale scores. Clinicians in our sample licensed between 6 to 15 or more than 30 years and those working in private outpatient settings had reduced odds of having moderate-high burnout, whereas those working 16 or more years had significantly increased odds for high CS scores. Responses to the open-ended question indicated workload demands and documentation as the top factors contributing to clinician burnout, while the connections with patients and coworkers help minimize such feelings. Conclusion: Individuals later in their career may develop protective factors to mitigate feelings of burnout compared to those early in their career. Also, clinicians working 40 or more hours per week may be more vulnerable to experiencing low-moderate CS and moderate-high burnout. Thus, individual clinicians and employers must evaluate personal, occupational, and systemic factors that contribute to reduced professional quality of life to inform preventive strategies for mitigating burnout.